Combined effect of flax fibers and steel fibers on spalling resistance of ultra-high performance concrete at high temperature - Zhang, Dong (2022)
This paper investigated the combined effects of flax fibers and steel fibers on spalling behavior, residual permeability, and compressive strength of ultra-high performance concrete (UHPC) after exposure to elevated temperature. Thermal analysis and microstructure observation were conducted to study the mechanism of the hybrid fibers in spalling prevention. The findings showed that the combined use of steel and flax fibers could completely prevent spalling of UHPC with relatively low fiber content, while solely using either steel fibers or flax fibers did not prevent spalling even with high fiber contents. The synergistic effect of hybrid flax and steel fibers on enhancing spalling resistance of UHPC was attributed to the increase in permeability from flax fibers and the bridging effect of steel fibers under elevated temperature. The mechanism of enhanced permeability of UHPC relied on two aspects: shrinkage of flax fibers at high temperature created interfacial gaps between the flax fibers and the matrix and microcracks created by the expansion of steel fibers enhanced the connectivity of these gaps and the microcracks. The bonding between steel fibers and matrix retained at a certain level at temperatures below 400 °C, which could also help mitigate spalling. It was also found that the combination of steel and flax fibers could compromise the reduction in compressive strength caused by the addition of flax fibers.